The comparison of internet pricing scheme in multi link bottleneck multi service network - Puspita, Fitri Maya; Seman, Kamaruzzaman; M. Taib, Bachok; Abdullah, Ismail (2017)
In this research we set up pricing scheme of multilink internet bottleneck for multi-service network by giving the modified models and the solution.This model is based on the local server data in Palembang.Internet Service Provider (ISP) requires the appropriate pricing schemes in order to maximize revenue and provide quality services that can satisfy the Internet users.The model established by setting the base price (α) as constants and the premium quality of service (β) as variables and constants.Then the model will be solved using Program LINGO 13.0 to obtain the optimal solution.From the results obtained shows the optimal solution that ISP can use the models to generate maximum revenue and gives options according to the user needs in accordance with the goal of ISP.The optimal solution results compared to previous work show that the larger dimension of the problem, the goals can also change according to the needs. From LINGO 13.0, the solution for four services and 3 links offered were maximized when we set up the base price (α) as constants and the premium quality of service (β) as constants for Ii = Ii-1. So ISP can use the modification scheme to achieve its goals.The realistic case to be solved by LINGO 13.0 is limited to have only four services and three links.